Molecular pathogenesis and heterogeneity in type 3 VWD families in U.S. Zimmerman program - Christopherson, Pamela A.; Haberichter, Sandra L.; Flood, Veronica H.; Perry, Crystal L.; Sadler, Brooke E.; Bellissimo, Daniel B.; Di Paola, Jorge; Montgomery, Robert R.; Abshire, T; Weiler, H; Lillicrap, D; James, P; et al. (Journal of thrombosis and haemostasis, 2022)
Background Type 3 von Willebrand Disease (VWD) is a rare and severe form of VWD characterized by the absence of von Willebrand factor (VWF). Objectives As part of the Zimmerman Program, we sought to explore the molecular pathogenesis, correlate bleeding phenotype and severity, and determine the inheritance pattern found in type 3 VWD families. Patients/Methods 62 index cases with a pre‐existing diagnosis of type 3 VWD were analyzed. Central testing included FVIII, VWF:Ag, VWF:RCo, and VWFpp. Bleeding symptoms were quantified using the ISTH bleeding score. Genetic analysis included VWF sequencing, comparative genomic hybridization and predictive computational programs. Results 75% of subjects (46) had central testing confirming type 3, while 25% were re‐classified as type 1‐Severe or type 1C. Candidate VWF variants were found in all subjects with 93% of expected alleles identified. The majority were null alleles including frameshift, nonsense, splice site, and large deletions, while 13% were missense variants. Additional studies on 119 family members, including 69 obligate carriers, revealed a wide range of heterogeneity in VWF levels and bleeding scores, even amongst those with the same variant. Co‐dominant inheritance was present in 51% of families and recessive in 21%, however 28% were ambiguous. Conclusion This report represents a large cohort of VWD families in the U.S. with extensive phenotypic and genotypic data. While co‐dominant inheritance was seen in approximately 50% of families, this study highlights the complexity of VWF genetics due to the heterogeneity found in both VWF levels and bleeding tendencies amongst families with type 3 VWD.